الآثار القانونيّة الناتجة عن التزامات العامل المهنيّة تجاه ربّ العمل - زعبي, عمار (University of Eloued جامعة الوادي, 2016)
عقد العمل هو عقد يلتزم العامل بمقتضاه بالعمل تحت إدارة وإشراف ربّ العمل. من أهمّ خصائص عقد العمل أنّه عقد رضائي، ملزم للجانبين وعقد معاوضة كما أنّه من عقود المدّة. يمنح عقد العمل العامل حقوقا كما يفرض عليه التزامات، وفي حال الإخلال بالالتزامات الملقاة على عاتقه فقد أقرّ القانون العديد من الآثار القانونية التي تسمح للطّرف الثاني في العقد وهو ربّ العمل من ضمان مصالحه. يتناول هذا المقال بالدراسة الآثار القانونية الناتجة عن التزامات العامل المهنيّة تجاه ربّ العمل في عقد العمل الفردي. Abstract : Labor contract is a contract pursuant thereto worker is committed to working under the direction and supervision of the employer, One of the main characteristics of Labor contract is that it is a consensual contract, bilateral contract, contract for a valuable consideration , and Labor contract gives the worker rights, and it imposes to him obligations. In case of breach of the obligations incumbent upon himself the law has approved many of the legal implications that will allow the second party in the contract which is the employer to ensure their interests. This article examines the legal effects arising from professional worker's obligations towards the employer in the labor contract
The legal effects arising from Professional worker's obligations towards the employer
مجلة البحوث والدراسات المجلد 13 العدد 01 جامعة الوادي
Keywords: العمل، المهنة، الالتزامات، رب العمل، العامل، الآثار القانونية; work, profession, obligations, employer, worker, legal effects